Application Value of a 6-Type Classification System for Common Hepatic Artery Absence During Laparoscopic Radical Resections for Gastric Cancer. Issue 32 (August 2015) - Huang, Chang-Ming; Chen, Rui-Fu; Chen, Qi-Yue; Wei, Jin; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; et al.
<x xml:space="preserve">Abstract</x> Abstract The common hepatic artery (CHA) is an important blood vessel that must be vascularized during D2 lymphadenectomies for gastric cancer. When the CHA is absent, the risk of vascular injury increases. To explore the anatomic classification of CHA absence and its application value in laparoscopic radical resections for gastric cancer. Clinical data were collected prospectively from 2170 gastric cancer patients from June 2007 to December 2013, and the data were analyzed retrospectively. The anatomy of CHA absence was assessed synthetically by combining preoperative CT scans and intraoperative images, which were classified according to the anatomy of replaced hepatic arteries (RHAs) and were grouped into the early-year group (2007–2011) and the later-year group (2012–2013) based on the year in which the operation was performed. CHA absence was noted in 38 cases (1.8%) and was classified into 6 types: type I (replaced CHA [RCHA] from the superior mesenteric artery [SMA] with retropancreatic course, 28), type II (RCHA from the SMA with circumambulated course, 1), type III (RCHA from the aortic artery, 1), type IV (replaced left hepatic artery [RLHA] from the left gastric artery [LGA] and replaced right hepatic artery [RRHA] from the SMA, 5), type V (RLHA from the LGA and RRHA from the celiac artery, 2), and type VI (RLHA from the aberrant gastroduodenal artery and RRHA from the SMA, 1). Of the 38 cases, 17 cases (44.7%) belong to the early-year group, and 21 cases (55.3%) belong to the later-year group. The vascular injury rate was significantly lower in the later-year group than in the early-year group (4.8% [1/21] vs 41.2% [7/17], P = 0.005]. Additionally, the alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBIL) values were significantly lower in the later-year group than in the early-year group on postoperative day 3 (all P < 0.05). A 6-type anatomic classification system can be used to demonstrate variations in features resulting from CHA absence in detail. Knowledge regarding a patient's classification is helpful for surgeons, and vascular injury and liver function damage may be reduced in patients who are properly classified prior to surgery.